A new conceptual cold-end design of boilers for coal-fired power plants with waste heat recovery. (1st January 2015) - Yang, Yongping; Xu, Cheng; Xu, Gang; Han, Yu; Fang, Yaxiong; Zhang, Dongke
Highlights: A new cold-end design of boilers for CFPPs with waste heat recovery is proposed. Thermodynamic and economic analyses are quantitatively conducted. Higher energy efficiency improvement and greater economic benefits are achieved. Lower exergy destruction and better matched energy level are obtained. Abstract: After conducting an in-depth analysis of the conventional boiler cold-end design for waste heat recovery, this work proposed a new conceptual boiler cold-end design integrated with the steam cycle in a 1000 MW CFPP, in which the preheating of air was divided into high-temperature air preheater (HTAP), main air preheater (MAP) and low-temperature air preheater (LTAP). The HTAP and an economizer were installed in separate flue ducts, and the low temperature economizer (LTE) was situated between the MAP and the LTAP in the main flue duct to heat the condensed water. In the proposed boiler cold-end design, the flue gas waste heat was not only used to heat condensed water, but also to further preheat the combustion air. The air temperature at the air-preheater outlet increases and part of the steam bleeds with high exergy can be saved, resulting in greater energy-savings and better economics. Results showed that, for a typical 1000 MW CFPP in China, using the proposed boiler cold-end design for waste heat recovery could produce 13.3 MWe additional net power output with a heat rate reduction of approximately 112.0 kJ/kW h and could yield a net benefit of up to 85.8 M per year, which is much greater than those of the conventional cases. Exergy destruction is also reduced from 49.9 MWth in the conventional boiler cold-end design to 39.6 MWth in the proposed design.